Hubungan Tingkat Stres Terhadap Peningkatan Risiko Terjadinya Dermatitis Atopik Pada Remaja di SMP Negeri 8 Surakarta - Lufita, Lita; , dr. Nurrachmat Mulianto, M.Sc., Sp.K.K; , dr. Ratih Pramuningtyas, Sp.KK (2015)
Background : Atopic Dermatitis (AD) is a chronic disease commonly in children. The number of Atopic Dermatitis prevalence in Indonesia is now three times higher making it five of the most common skin disease. Atopic Dermatitis is mostly caused by genetic factor and certain environment including neurogenus factor and immunology. Of many factors associated with Atopic Dermatitis. Psychological stress can cause Atopic Dermatitis highten the severity of Atopic Dermatitis symptoms. Objective :To find out relationship between stress level to the severity of Atopic Dermatitis symptoms in teenagers, student of SMPN 8 Surakarta. Methods : This research use analytic observational study design with cross sectional approach. The subject 46 responden. Results : Based on characteristic subject of research is student of SMPN 8 Surakarta the analisis of data has been optained using corelation of Pearson test showed ρ value = 0.037 (ρ value < 0.05). Conclusion : There are relationship between stress level to the occurence of atopic dermatitis in teenagers, student of SMPN 8 Surakarta.